2013
DOI: 10.1016/j.diabres.2012.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Problem solving interventions for diabetes self-management and control: A systematic review of the literature

Abstract: Aims Problem solving is deemed a core skill for patient diabetes self-management education. The purpose of this systematic review is to examine the published literature on the effect of problem-solving interventions on diabetes self-management and disease control. Data Sources We searched PubMed and PsychINFO electronic databases for English language articles published between November 2006 and September 2012. Reference lists from included studies were reviewed to capture additional studies. Study Selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 31 publications
(221 reference statements)
3
69
0
Order By: Relevance
“…These findings are consonant with other reports in the United States and worldwide [8]. Diabetes self-care management involves the interrelation of multiple behaviors and tasks [9]. Adherence to the complex diabetes self-care behaviors is a major barrier to achieve and sustain glycemic control.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are consonant with other reports in the United States and worldwide [8]. Diabetes self-care management involves the interrelation of multiple behaviors and tasks [9]. Adherence to the complex diabetes self-care behaviors is a major barrier to achieve and sustain glycemic control.…”
Section: Discussionsupporting
confidence: 88%
“…The latter has been noted in a survey of diabetes educators. They reported that appropriate problem-solving was the most difficult skill to teach patients [23,24]. A large trial in asthmatic adults showed no benefits of problem-solving education, and the authors suggested that patients' lack of motivation to achieve high adherence was the main reason for this failure [25].…”
Section: Discussionmentioning
confidence: 96%
“…Their work highlighted a synthesis of diabetes education and behavior change strategies. In addition to this early work, several reviews exist on the effectiveness of problem solving interventions [3,37] and those papers can be accessed for complete information on the findings. Problem solving interventions are popular with children and adults, and people with Type 1 or Type 2 diabetes.…”
Section: What Does Workmentioning
confidence: 99%